The Impact of Intellectual Capital toward Firm’s Profitability and Market Value of Retail Companies Listed in Indonesia Stock Exchange (IDX) from 2013-2016 - Richard Suherman (iBuss Management, 2017)
Nowadays, as we move from labor intensive economies to knowledge intensive economies, companies need a new source of competencies to compete with other. Investing in tangible asset is no longer sustainable and it is no longer a factor that differentiate between companies. This conditions encorage the researcher to find other competencies that could give companies new competitive advantage in order to improve their profitability and market value. The researcher will focus on intellectual capital as the main driver that could improve company’s profitability and market value. Intellectual capital itself consists of three components, namely, human capital, structural capital, and relational capital. The researcher would like to know whether intellectual capital and its components could improve company’s profitability and market value.The data was collected from 10 retail companies that are listed in Indonesia Stock Exchange (IDX) during the period of 2013-2016. The researcher’s findings shows that intellectual capital have a significant impact toward firm’s profitability and have an insignificant impact toward market value. Further test conducted on the components of intellectual capital also shows that only human capital has a significant impact toward firm’s profitability and only human capital and structural capital have a significant impact toward market value.           Keywords: Intellectual Capital, Human Capital, Structural Capital, Relational Capital, Operating Profit Margin, Market Value